1999
DOI: 10.1590/s0004-282x1999000600020
|View full text |Cite
|
Sign up to set email alerts
|

Kearns-Sayre syndrome "plus": classical clinical findings and dystonia

Abstract: We present a boy of eight years of age with symptoms of Kearns-Sayre syndrome (KSS) characterised by ophthalmoparesis, palpebral ptosis, mitochondrial myopathy, pigmentous retinitis, associated to short stature, cerebellar signs, cardiac blockade, diabetes mellitus, elevated cerebrospinal fluid protein concentration, and focal hand and foot dystonia. The skeletal muscle biopsy demonstrated ragged red fibers, cytochrome C oxidase-negative and succinate dehydrogenase-positive fibers. The magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…Leigh syndrome is genetically and biochemically heterogeneous and has been reported in association with complex I, complex IV and complex V defects (Hanna and Bhatia 1997). Dystonia has been also reported in association with the primary LHON mutations G14459A, T14459A, T14596A, and G11778A, with or without blindness (Jun et al 1994;Shoffner et al 1995;De Vries et al 1996;McFarland et al 2007), the MELAS mutation A3243G (Sudarsky et al 1999) and in association with Kearns-Sayre syndrome (Marie et al 1999). A novel C4716G mutation has been described recently in patients with dystonia, bilateral basal ganglia lesions, epilepsy, and ptosis (McFarland et al 2007).…”
Section: Respiratory Chain Disorders (Rcds)mentioning
confidence: 99%
“…Leigh syndrome is genetically and biochemically heterogeneous and has been reported in association with complex I, complex IV and complex V defects (Hanna and Bhatia 1997). Dystonia has been also reported in association with the primary LHON mutations G14459A, T14459A, T14596A, and G11778A, with or without blindness (Jun et al 1994;Shoffner et al 1995;De Vries et al 1996;McFarland et al 2007), the MELAS mutation A3243G (Sudarsky et al 1999) and in association with Kearns-Sayre syndrome (Marie et al 1999). A novel C4716G mutation has been described recently in patients with dystonia, bilateral basal ganglia lesions, epilepsy, and ptosis (McFarland et al 2007).…”
Section: Respiratory Chain Disorders (Rcds)mentioning
confidence: 99%
“…Brainstem MRI abnormalities were identified by several authors in a few cases. 25,26 Kapeller et al 11 reported abnormalities in glossopharyngeal nuclei in a patient with dysphagia, and Chu et al 25 reported brainstem hyperintensity in two patients. On the other hand, CbA was frequently identified in patients with KSS.…”
Section: Commentmentioning
confidence: 99%
“…Em revisão feita por Berenberg et al, apud Marie et al, incluindo cinco casos de sua casuística e mais 30 da literatura, BAVT foi a causa de morte em 20% dos pacientes. 9 A grande maioria dos estudos mostrou melhora clínica, e estes são mais recentes quando comparados com estudos que não demonstraram a eficácia da CoQ 10. No caso relatado, ocorreu melhora clínica significativa dos sintomas de fadiga muscular relatados pelo paciente e contribuiu para uma sutil melhora do quadro de oftalmoplegia.…”
Section: Discussionunclassified